Antioxidant Activity and Melanogenesis Inhibitory Effect of Acerola Fruit (Malpighia glabra L.) Aqueous Extract and Its Safe Use in Cosmetics - Wang, Ling; Li, Fuheng; He, Congfen; Dong, Yinmao; Wang, Qi (Asian Journal of Chemistry, 2015)
Acerola (Malpighia glabra L.) fruit is well known as an excellent dietary source of vitamin C and many other phytochemicals. We investigated the effects of aqueous extract of acerola fruit on melanogenesis in B16 mouse melanoma cells and antioxidant activity. Aqueous extract of acerola fruit significantly reduced the cellular melanin level and inhibited tyrosinase activity in a concentration-dependent manner. 1,1-Diphenyl-2-picrylhydrazyl (DPPH) scavenging tests indicated that aqueous extract of acerola fruit has potent antioxidative activity. These results suggested that aqueous extract of acerola fruit might be effective in skin-whitening and that its inhibitory effect on melanogenesis is due to a decrease in intracellular tyrosinase as determined by levels of gene expression (mRNA) and enzyme activity. The hemolysis rate after exposure to aqueous extract of acerola fruit was less than 10 %, below the 20 % regulatory limit for the red blood cell test. No allergic reactions were observed in the human skin patch tests. Hence, aqueous extract of acerola fruit could become an effective component in antiaging foods and whitening cosmetics.